Teknik Bibliokonseling dalam Bimbingan Kelompok - Habsy, Bakhrudin All; Malika, Avrie Dzakkiya; Lena, Annora Malva; Rahma, Nabila Faza (TSAQOFAH, 2024)
Bibliocounseling technique in the context of counseling guidance is an approach that utilizes reading media, such as books, to facilitate interaction between counselors and counselees. The purpose of this study is to assist counselees in anticipating and overcoming various challenges that they may face in the future. In addition, this method is also proven effective in improving learners' ability to identify, respond to, and overcome potential problems more independently and proactively. The research method used is a literature study, which involves searching various sources such as journals, articles, theses, and other reading materials. The results concluded that the use of bibliotherapy techniques in group guidance can provide a deeper understanding and improve learners' ability to deal with potential problems in the future.